2022
DOI: 10.3390/children9071048
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Differing Language Background Exposures on Bayley-III Language Assessment in a National Cohort of Children Born Less than 29 Weeks’ Gestation

Abstract: Preterm infants are at risk for adverse neurodevelopmental outcomes, especially language delay. Preterm infants < 29 weeks’ gestational age, cared for in Canadian Neonatal Follow-Up Network affiliated hospitals, were assessed between 18 to 21 months corrected age using the Bayley-III. Bayley-III Language Composite Scores were compared using univariate and multivariate analyses for children in three primary language groups: English, French and other. 6146 children were included. The primary language at home … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 43 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…reported that children with multilingual exposure outperformed their monolingual preterm peers. Contrastingly, BSID‐III scores were lower among bilingual French–English speakers in a cohort of preterm according to Chan et al 2 . Nevertheless, there is data that suggests bilingualism among young children can lead to slower rates of language development in both languages 27 .…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…reported that children with multilingual exposure outperformed their monolingual preterm peers. Contrastingly, BSID‐III scores were lower among bilingual French–English speakers in a cohort of preterm according to Chan et al 2 . Nevertheless, there is data that suggests bilingualism among young children can lead to slower rates of language development in both languages 27 .…”
Section: Discussionmentioning
confidence: 87%
“…Studies have shown that this delay is secondary to a combination of biological and environmental factors including a critical period of brain development and prolonged hospitalisation in neonatal intensive care unit (NICU) 1 . This topic of language development has previously been explored in extremely PT infants from Spanish‐speaking homes and PT infants from bilingual French–Canadian English cohorts 1,2 . In a cohort of EPT children at age 2 years, Lowe et al 1 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations